Caloric Vestibular Stimulation as a Treatment for Conversion Disorder: A Case Report and Medical Hypothesis - Noll-Hussong, Michael; Holzapfel, Sabrina; Pokorny, Dan; Herberger, Simone (Frontiers in Psychiatry, 2014)
Conversion disorder is a medical condition in which a person has paralysis, blindness, or other neurological symptoms that cannot be clearly explained physiologically. To date, there is neither specific nor conclusive treatment. In this paper, we draw together a number of disparate pieces of knowledge to propose a novel intervention to provide transient alleviation for this condition. As caloric vestibular stimulation (CVS) has been demonstrated to modulate transiently a variety of cognitive functions associated with brain activations, especially in the temporal-parietal cortex, anterior cingulate cortex, and insular cortex, there is evidence to assume an effect in specific mental disorders. Therefore, we go on to hypothesize that lateralized cold vestibular caloric stimulation will be effective in treating conversion disorder and we present provisional evidence from one patient that supports this conclusion. If our hypothesis is correct, this will be the first time in psychiatry and neurology that a clinically well-known mental disorder, long considered difficult to understand and to treat, is relieved by a simple or common, non-invasive medical procedure.